Elderly Care: Policy Initiatives and Older Parents’ Perception in Nepali Society - Upadhyay, Chandra (Rupantaran: A Multidisciplinary Journal, 2021)
Elderly care in the present day Nepali society is affected with the changes in the family arrangements. The old age situations without children, children away from home, and out migration of children create impacts on the maintenance and care of the elderly parents. The major issues of apprehension with the elderly population are their health status including their social, psychological and emotional conditioning, and elderly support activities. Based on focused group discussions and analysis of the selected narratives collected through personal interviews in Province-1, this paper finds, more or less, a common perspective of the elderly parents that their life situations become lonelier and difficult as they become older and feel helpless in absence of their children. Social inclusion and integration of senior citizens have been two major aspects in the state policy interventions while the daily life issues and activities of the elderly are of equal concern. The initiatives for elderly care shall be based on their interest, choices and needs.